Postdiagnostic physical activity, sleep duration, and TV watching and all-cause mortality among long-term colorectal cancer survivors: a prospective cohort study - Ratjen, Ilka; Schafmayer, Clemens; di Giuseppe, Romina; Waniek, Sabina; Plachta-Danielzik, Sandra; Koch, Manja; Burmeister, Greta; Nöthlings, Ute; Hampe, Jochen; Schlesinger, Sabrina; Lieb, Wolfgang (BMC cancer, 2017)
Background Lifestyle recommendations for cancer survivors are warranted to improve survival. In this study, we aimed to examine the association of total physical activity, different types of physical activity, hours of sleeping at day and night, and hours spent watching television (TV) with all-cause mortality in long-term colorectal cancer (CRC) survivors. Methods We assessed physical activity in 1376 CRC survivors (44% women; median age, 69 years) at median 6 years after CRC diagnosis using a validated questionnaire. Multivariable-adjusted Cox regression models were used to estimate hazard ratios (HRs) for all-cause mortality according to categories of physical activities, sleep duration, and TV watching. Results During a median follow-up time of 7 years, 200 participants had died. Higher total physical activity was significantly associated with lower all-cause mortality (HR: 0.53; 95% CI: 0.36–0.80, 4th vs. 1st quartile). Specifically, sports, walking, and gardening showed a significant inverse association with all-cause mortality (HR: 0.34; 95% CI: 0.20–0.59, HR: 0.65; 95% CI: 0.43–1.00, and HR: 0.62; 95% CI: 0.42–0.91, respectively for highest versus lowest category). Individuals with ≥2 h of sleep during the day had a significantly increased risk of all-cause mortality compared to individuals with no sleep at day (HR: 2.22; 95% CI: 1.43–3.44). TV viewing of ≥4 h per day displayed a significant 45% (95% CI: 1.02–2.06) higher risk of dying compared to ≤2 h per day of watching TV. Conclusions Physical activity was inversely related to all-cause mortality; specific activity types might be primarily responsible for this association. More hours of sleep during the day and a higher amount of TV viewing were each associated with higher all-cause mortality. Based on available evidence, it is reasonable to recommend CRC survivors to engage in regular physical activity.